Evaluation of some botanicals and microbial bioformulations against grey blight disease of tea (Camellia sinensis) - BORA, POPY; BORA, L C; BHUYAN, R P (The Indian Journal of Agricultural Sciences, 2021)
Grey blight disease of tea (Camellia sinensis) is considered as a major threat to tea plantation owing to adverse affect on yield and quality parameters in tea. In the present study, an effort was made to explore some botanicals and microbial formulations for management of grey blight disease under field condition in the pretext of growing demand of organic tea. Seven botanicals at three concentrations (5.0, 10.0 and 15.0%) and four microbial bioformulations were screened in vitro against Pestalotiopsis theae, the grey blight pathogen. Of the botanicals, significant inhibition was recorded by water extract of Xanthium strumarium and Pongamia pinnata at 15% concentration. Biogreen 5 (Formulation of Trichoderma viride, Pseudomonas fluorescens, Bacillus thuringiensis, Beauveria bassiana and Metarhizium anisoplae) and Bioveer (T. viride) among the bioformulations recorded highest reduction in mycelial growth of pathogen. The two most effective botanicals and bioformulations screened in vitro were further evaluated individually and in combination under field condition for two consecutive seasons. Lowest percent disease incidence (5.23%) was recorded with combination of Biogreen 5 and Bioveer followed by Bioveer alone (7.79%) at 150 days of spray. Foliar spray of X. strumarium and P. pinnata in combination also showed satisfactory reduction in grey blight incidence with PDI of 17.97%. The study revealed that both bioagents and botanicals could be an ecofriendly and sustainable solution for grey blight disease management under organic tea production system.